Ceramic Production and the Development of Complex Polities in Late Prehistoric Southwestern Iran - Berman, Judith Carol (2012)
Ph.D. Dissertation. Three volumes; Adviser: Gregory A. Johnson. Order No. DA8614657; cf. DissAbstr 47/04 (October 1986) 1379- A.